Short-term responses of soil nutrients and enzyme activities to nitrogen addition in a Larix principis-rupprechtii plantation in North China - Yang, Xiaocong; Yang, Liu; Li, Qianru; Li, Xiao; Xu, Guoqiao; Xu, Zhongqi; Jia, Yanlong (Frontiers in Ecology and Evolution, 2023)
Atmospheric nitrogen (N) deposition is among the main manifestations of global change and has profoundly affected forest biogeochemical cycles. However, the threshold of N deposition to soil nutrient contents and enzyme activities have rarely been studied in a forest. We here explored the effects of N deposition on soil nutrients and enzyme activities in the Larix principis-rupprechtii plantation on the northern Yanshan Mountain through multigradient N addition experiments (0, 5, 10, 20, 40, 80, and 160 kg N ha−1 yr−1) after fertilization for 2 years. Compared with the controls, N addition first led to a decrease in soil NH4+-N and NO3−-N, which then increased significantly. N addition had no significant effects on other soil nutrients. N addition overall elevated soil β-glucosidase activity. N application of >40 kg N ha−1 yr−1 significantly reduced soil leucine aminopeptidase activity, but had no significant effects on soil acid phosphatase, N-acetyl-β-D-glucosidase, and urease activities. N addition increased the overall stoichiometry ratio of EEA C:N and EEA C:P, but EEA N:P started decreasing after N application of 40 kg N ha−1 yr−1. The ratios of C, N, and P acquisition activities changed from 1:1.2:1 under the control conditions to 1:1.1:1 under N application of 160 kg N ha−1 yr−1. N addition increased the overall vector length and had no significant effects on the vector angle. Correlation and redundancy analyses revealed that N addition-induced change in available soil N was the main factor affecting soil enzyme activity and stoichiometry. In general, different enzyme activities had different sensitivities to N addition. Moderate N addition or atmospheric N deposition (e.g., <40 kg N ha−1 yr−1) had beneficial effects on soil nutrient cycling and microorganisms in Larix principis-rupprechtii plantation.